Effect of supplementation with different protein sources on digestibility and rumen metabolites of Yankasa rams - Abu, H.T.; Otaru, S.M.; Yashim, S.M.; Musa, A (Nigerian Journal of Animal Science, 2023)
A study was conducted to evaluate the dietary inclusion of cottonseed cake (CSC), sun dried poultry litter (SDPL) and dried cassava leaf meal (DCLM) on digestibility and rumen metabolites of Yankasa rams. Eighteen (18) grower Yankasa rams, weighed 11.5 to 15.5 kg were used to measure the rumen metabolites, nutrient digestibility and nitrogen balance of the rams. The chemical analysis result showed that treatment COSM or POUT diets had higher values of crude protein than CASM diet. Total dry matter intake was similar (P>0.05) for all the treatments. Rumen parameters were significantly (P<0.05) affected by the nitrogen sources in such a way that rumen pH 4 h after feeding was highest (6.50) in animals fed CASM diet and lowest for the COSM fed animals. Temperature values before feeding was highest (37.38OC) in POUT fed animals and lowest (34.38OC) in COSM fed animals, the total volatile fatty acid values 4 h after feeding was 42.75 and 28.25 for animals fed POUT diet and COSM diet, respectively. Nutrient digestibility was significantly (P <0.05) different on digestibility of nitrogen free extract. Nitrogen intake was significantly (P <0.05) higher in rams fed COSM (52.71 g/d) or POUT (48.72 g/d) diet compared to their counterpart fed CASM diet. Nitrogen balance and nitrogen absorbed were statistically similar (p>0.05) for all the groups. It could be concluded that CSC, SDPL and DCLM is a safe nitrogen sources for rams without any determinant effects.